2008
DOI: 10.1063/1.2828709
|View full text |Cite|
|
Sign up to set email alerts
|

Coherent heterodyne time-domain spectrometry covering the entire “terahertz gap”

Abstract: Terahertz waves, electromagnetic radiation in the spectral region commonly defined between 0.3 and 10THz, allow innovative sensing and imaging techniques that can provide spectroscopic information unavailable at other wavelengths. However, simultaneously intense, broadband, and coherent spectroscopic measurement remains challenging. We report spectrometry using gases ionized by femtosecond pulses to generate and sense broadband terahertz pulses. Using a coherent heterodyne technique, the measurements span the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
169
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 325 publications
(173 citation statements)
references
References 15 publications
0
169
0
1
Order By: Relevance
“…[62,63] generation of the second-harmonic field by the four-wave mixing process can be used to measure the temporal dependence of the THz electric field. In the detection stage ( Figure 5) both the THz and the probe beam with frequency ω are focused between two needle or plate shaped electrodes having a small separation of the order of 1 mm [63]. The intensity is kept just below the plasma formation threshold.…”
Section: 3detection Of Thz Waves In Gasesmentioning
confidence: 99%
“…[62,63] generation of the second-harmonic field by the four-wave mixing process can be used to measure the temporal dependence of the THz electric field. In the detection stage ( Figure 5) both the THz and the probe beam with frequency ω are focused between two needle or plate shaped electrodes having a small separation of the order of 1 mm [63]. The intensity is kept just below the plasma formation threshold.…”
Section: 3detection Of Thz Waves In Gasesmentioning
confidence: 99%
“…Electro-optic sampling [42] is effective to detect low frequency components (<1000 cm −1 ). We performed an air-biased coherent detection scheme [43] for the electro-optic sampling. The schematic of the system is shown in Figure 1(b).…”
Section: Electro-optic Samplingmentioning
confidence: 99%
“…A THz wave having a peak intensity of the order of hundreds of kV/cm has recently been demonstrated using a pulsed laser [3,4]. It has been found that the irradiation of a periodically oscillating THz wave causes photon-mediated tunneling in quantum wells (QWs), superlattices (SLs), and Wannier-Stark ladders (WSLs).…”
Section: Introductionmentioning
confidence: 99%
“…However, as F ac is enhanced to the intense region of the order of hundreds of kV/cm, it can be hypothesized that a large number of PSBs contribute to this coupling, invalidating the conventional interpretation mentioned above. Further, state-of-the-art THz light sources that can realize such intensities have already been produced [3,4], as mentioned above.…”
Section: Introductionmentioning
confidence: 99%